Carga de vento atuante em uma estufa agrícola no município de Alegrete - RS - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Agriculture in Brazil is, historically, one of the main bases of the country's economy, and needs investment and diversification in the types of production system, enabling income generation and subsistence to rural producers, in order to keep up with the development of the increasingly competitive agricultural sector. In this work, a study was performed on the load acting on an agricultural greenhouse, mainly due to the wind action, from a structure installed in the city of Alegrete - RS, specifically on the campus of the Universidade Federal do Pampa, which has recurrent failures caused by the wind action, seeking to verify, in this way, the requesting efforts due to the static wind actions, according to the Brazilian standards of wind actions on structures - ABNT NBR 6123 (1988) and the specific standard for agricultural greenhouses - NBR 16032 (2012). With this, it was analyzed characteristics of the already installed rural construction, construction methods, situation of its implementation on site and aspects of the local climate and terrain. Studies and analysis of the agricultural greenhouse arch structure were carried out, finding the obstruction pressure, from the characteristic velocity, which made it possible to verify the total pressure coefficients, internal pressure coefficient and external pressure coefficients, by the existing standards, in order to perform the comparison of the results found. It was possible to verify that the ABNT NBR 6123 (1988) standard, resulted in higher ultimate load values compared to NBR 16032 (2012), at most points, reaching 531 kgf.m-1 at specific locations on the greenhouse roof (for oblique wind), while the specific greenhouse standard resulted in approximately 372 kgf.m-1 for the same region. Keywords: Protected cultivation, wind action, strctures, Rural buildings.
Keywords: Engenharia agrícola; Construções rurais; Alegrete - RS; Agricultural engineering; Rural buildings; CNPQ::CIENCIAS AGRARIAS